St. Lucia : Request for Disbursement under the Rapid Credit Facility and Emergency Natural Disaster Assistance-Staff Report, Staff Supplement, Press Release and Statement by the Executive Director for St. Lucia. (IMF Staff Country Reports; Country Report, 2011)
St. Lucia faces significant policy challenges in the aftermath of Hurricane Tomas. It is experiencing an urgent balance of payments need that would result in a severe economic disruption. The government is focused on achieving medium-term debt sustainability. The policies outlined tackle urgent rebuilding needs and appropriately aim to maintain macroeconomic stability. Executive Directors support the request for funds based on the extent of the damage caused, the associated urgent balance of payments need, and the government's commitment to limit the increase in capital spending.